Assessing children's needs and circumstances : the impact of the assessment framework - Cleaver, Hedy (Jessica Kingsley, 2004)
Drawing on in-depth interviews with social workers and their managers, and families and young people themselves, the authors of this important book show how the principles embodied in the Assessment Framework have been applied to social work practice. Revisiting the principles outlined in the legislative context and the Assessment Framework, they show how the focus on assessment has affected the work with children, and the experiences of children and families themselves. The authors identify a range of issues that influence the implementation of the Assessment Framework, including the key area.